Socio-Cultural Contributions in Mediating the Influence of Principal Supervision on Teacher Performance - Ivan Fanani Qomusuddin; Sam'un; Siti Latifah; Mohamad Erihadiana (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
This study aims to analyze the influence of principal supervision on teacher performance mediated by socio-cultural factors. The research uses a quantitative approach with a survey method. The population of this study is elementary school teachers of the Regional Education Corps of Sindangkasih District, Ciamis Regency which totals 86 teachers. The data collection technique uses a questionnaire through google form media. The data analysis technique uses Structural Equation Modeling (SEM) with the help of Lisrel 8.8 software. The results showed that the supervision of the principal had a significant influence of 70% on teacher performance, but when mediated by socio-cultural, the influence was only 9.8%. This shows that although socio-cultural values, such as work culture, social relationships, and norms in schools, contribute to teacher performance, their role is still relatively small compared to the direct influence of the principal's supervision. These findings show that socio-cultural has not been fully integrated as a strong supporting factor in the relationship between principal supervision and teacher performance.